Analisis Kualitas Layanan, Kemampuan Dan Kinerja Pengurus Pokjar Terhadap Kepuasan Mahasiswa di UPBJJ-UT Palangka Raya - Rahmaddian Rahmaddian; Stefani Made Ayu Artharini Koesanto; Deni Surapto (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Open University of Palangka Raya (UPBJJ-UT of Palangka Raya) has acknowledged the education-attainment gap between rural and urban areas, and officials have determined ways to connect with students in the far corners of Central Kalimantan. UPBJJ-UT of Palangka Raya has set up study groups (PokJar) through which non urban students acquire university education. Due to its wide range of locations and heterogeneous student populations, PokJar is established through management partnership that constitutes a governing body that oversees the district-wide operation and the delivery of the continuing education programs. On this optimistic basis, the service provided by PokJar administrators becomes central to optimizing quality education in a learning environment where the administrators and students are physically separated. However, the complexity of PokJar service and administrator performance may link to negative perceptions among students. Recognizing the nature of challenges facing PokJar management is expected to usher in the planning of improvement crucial to organizational development that is effective, efficient, accountable, responsive and transparent. This study taps into the quality service, the competence and performance of PokJar administrators of UPBJJ-UT of Palangka Raya in terms of student-perceived values using PLS-SEM method. The overall results address favorable responses, strongly suggesting a good measure of how PokJar administrators’ service, competence and performance meet student expectation.